Most Frequent Musculoskeletal Manifestation of Systemic Lupus Erythematosus Patients in Dr. Hasan Sadikin General Hospital Bandung - Sutrisno, Rahadian Nugi; Rahmadi, Andri Reza; Novita, Nita; Hamijoyo, Laniyati (Indonesian Rheumatology Association, 2017)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease with wide range of clinical symptoms. The patients frequently complain musculoskeletal involvement during the active state of the disease. Musculoskeletal manifestation in SLE patients is an important sign in making early diagnosis and monitoring treatment response. This study aims to determine the presentation of musculoskeletal involvement of SLE patients in Dr. Hasan Sadikin General Hospital Bandung.Methods: a descriptive cross-sectional quantitative study done by interviewing SLE patients concerning musculoskeletal manifestation as the primary data and tracking their medical record as the secondary data. Study was conducted between September to November 2016 in Rheumatology Clinic Dr. Hasan Sadikin General Hospital Bandung.Result: Ninety-seven SLE patients, 91 females (93,81%) and 6 males (6,19%), were enrolled in this study with mean age 35.12 (Â±10.91) years. The three highest proportions of muskuloskeltal manifestations were arthritis of the knee (84,5%), myalgia of upper back(40,2%), and muscle weakness (15,5%). We did not find any Jaccoudâs Arthropathy (JA) and tendinitis manifestation. Osteoporosis were occured in 4 patients (4,12%), whereas gout arthritis, spondytlitis, osteoarthritis, rotator cuff syndrome, and rhupus wereonly occured in one patient (1,03%), respectively.Conclusion: The common musculoskeletal manifestation in SLE patients were arthritis of knee, myalgia of upper back, and muscle weakness. Only small portion of patients suffered from osteoporosis, gout arthritis, spondytlitis, osteoarthritis, rotator cuff syndrome, and rhupus.Keyword: musculoskeletal manifestation, musculoskletal involment, SLE